Hardiness Ibu Tunggal: Studi Fenomenologis pada Ibu Tunggal yang Cerai Hidup dan Cerai Mati - Azizah, Nyimas Kholifatul; Septiningsih, Dyah Siti (Universitas Muhammadiyah Purwokerto, 2022)
Hardiness, a key personality trait, can play a crucial role in helping individuals manage stress effectively. This study aimed to explore the concept of hardiness among divorced and widowed single mothers. Employing a phenomenological approach with qualitative methodology, the research utilized semi-structured interviews to gather data, which was then analyzed through Interpretative Phenomenological Analysis (IPA). To ensure the credibility of the findings, triangulation, peer debriefing, and member checks were implemented. The study revealed that the four participants—single mothers who were either divorced or widowed—demonstrated strong hardiness. This trait enabled them to overcome significant challenges, view their children as a source of motivation and purpose, and transform past experiences into personal growth. The findings underscore the importance of hardiness in managing the stresses associated with single motherhood. It is recommended that interventions and support programs be developed to enhance hardiness among single mothers. Such programs could include targeted counseling, resilience training, and peer support groups designed to build coping skills and emotional resilience.